Ventricular Systolic Reserve in Asymptomatic Children Previously Treated With Low Doses of Anthracyclines - Guimaraes-Filho, Fabio; Tan, Doralice; Braga, Joao; Rodrigues, Alexandre; Waib, Paulo; Matsubara, Beatriz [UNESP] (Elsevier, 2007)
Doppler echocardiography has been used for the diagnosis of anthracycline-induced cardiotoxicity. However, few data are available that include asymptomatic children previously treated with a low cumulative dose of this drug and therefore have a low risk of cardiac dysfunction. The aim of this study was to evaluate after-exercise cardiac function in asymptomatic children previously treated with a low cumulative dose of anthracycline and no clinical or laboratory evidence of cardiotoxicity. Doppler echocardiography was performed before and immediately after physical exercise in 29 children aged 5 to 17 years (anthracycline [ADRIA] group). All had finished cancer treatment with anthracycline derivatives for ≥1 year (cumulative dose 100 mg/m2). Results were compared with those from age- and gender-matched healthy children (control group; n = 26) using the Mann-Whitney rank test. Exercise-induced cardiac function changes within groups were analyzed using Wilcoxon's signed-rank test. Exercise induced significant increases in left ventricular systolic function indexes in both groups. However, the ADRIA group had significantly lower changes in left ventricular ejection fraction (ADRIA group 0.71 ± 0.02 vs 0.80 ± 0.04 and control group 0.71 ± 0.02 vs 0.89 ± 0.05, p = 0.0017) and end-systolic stress-volume index (ADRIA group 4.59 ± 0.69 vs 6.4 ± 2.0 g.cm-2/ml.m-2 and control group 5.49 ± 0.98 vs 11.54 ± 2.86 g.cm-2/ml.m-2; p <0.0001), indicating decreased functional systolic reserve. In conclusion, asymptomatic children previously treated with low cumulative doses of anthracycline had decreased functional systolic reserve evidenced by exercise, suggesting a nonclinically manifested cardiotoxicity. © 2007 Elsevier Inc. All rights reserved.
Keywords: anthracycline; daunorubicin; doxorubicin; adolescent; child; clinical article; controlled study; Doppler echocardiography; exercise; female; heart function; heart left ventricle ejection fraction; heart left ventricle performance; human; low drug dose; male; priority journal; rank sum test; treadmill exercise; treatment duration; Wilcoxon signed ranks test; Adolescent; Anthracyclines; Antibiotics, Antineoplastic; Case-Control Studies; Child; Child, Preschool; Cross-Sectional Studies; Echocardiography, Doppler; Exercise Test; Female; Heart Function Tests; Humans; Male; Systole; Ventricular Dysfunction, Left